2008
DOI: 10.1021/bc700482u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Near-Infrared (NIR) Dye−Herceptin Conjugates as Photoacoustic Computed Tomography (PCT) Probes for HER2 Expression in Breast Cancer

Abstract: We are evaluating PCT imaging in conjunction with NIR-dye labeled Herceptin antibody for noninvasive assessment of HER2 expression in tumors. Herceptin was labeled with Alexa Fluor-750 amine reactive dye for characterization of photoacoustic and fluorescence signals. Measurements were performed in solution and after incubation in cultured cell lines that were positive or negative in expression of HER2. The dye to antibody ratio was controlled to achieve a broad range of degree of labeling (DOL = 2 to 15). Phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 21 publications
0
44
0
1
Order By: Relevance
“…In the bioconjugation reaction the succinimidyl ester group of NIR-dye reacts with a lysine residue of the mAb to form a stable peptide linkage. 15 After 2 h of reaction, the conjugate was purified on a G25 size exclusion column and the product was collected in fractions (Figure 1). Early-front and late-tail fractions from the column (Figure 1) were discarded due to low protein concentration and possible mixing of free dye into the conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…In the bioconjugation reaction the succinimidyl ester group of NIR-dye reacts with a lysine residue of the mAb to form a stable peptide linkage. 15 After 2 h of reaction, the conjugate was purified on a G25 size exclusion column and the product was collected in fractions (Figure 1). Early-front and late-tail fractions from the column (Figure 1) were discarded due to low protein concentration and possible mixing of free dye into the conjugate.…”
Section: Resultsmentioning
confidence: 99%
“…In other non-CT work, Herceptin has been used for targeted imaging using radioactivity [22], radioactive liposomes [18], magnetic nanoparticles [24], gadolinium [24][25][26] 18 F-PET [27], fluorophores [28][29][30] and near-infrared probes [28,31,32]. Consistent with these studies, we found a tumour uptake value (8.3% id g -1 ) similar to these other Herceptin adducts, indicating that the 15 nm AuNP-antibody conjugate delivery does not substantially alter the tumour uptake compared with, for example, a radiolabelled Herceptin antibody targeted to BT474 tumours, which showed 7.8% id g -1 localisation [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are many bio-compatible dyes that absorb in the optical window, including Indocyanine Green (ICG), 44 IRDye800CW, 101 AlexaFluor 750, 5 and methylene blue, 99 which all have been used in PA imaging. These dyes are typically small molecules-on the order of 1 nm-and are able to quickly clear the body through the renal system.…”
Section: Dyesmentioning
confidence: 99%
“…In addition to the ICG PEBBLEs, dyes can be directly conjugated to molecular targeting agents. 5,101 Furthermore, a fluorescent activatable molecular probe named MMPSense 680 can also be used for molecular imaging. While in its inactivated state, it does not fluoresce, but, when activated by a matrix metalloproteinase (MMP), the agent fluoresces and its absorption spectrum changes, producing a unique PA signature.…”
Section: Dyesmentioning
confidence: 99%